Impact of aerobic fitness status, menstrual cycle phase, and oral contraceptive use on exercise substrate oxidation and metabolic flexibility in females - Olenick, A. A.; Pearson, R. C.; Jenkins, N. T. (Applied Physiology, Nutrition, and Metabolism, 2024)
The influence of menstrual cycle phase and fitness status on metabolism during high-intensity interval exercise (HIIE) was assessed. Twenty-five females (24.4 (3.6) years) were categorized by normal menstrual cycle (n = 14) vs. oral contraceptive (OC) use (n = 11) and by aerobic fitness, high-fitness females (HFF; n = 13) vs. low-fitness females (LFF; n = 12). HIIE was four sets of four repetitions with a 3 min rest between intervals on a cycle ergometer at a power output halfway between the ventilatory threshold and VO2peak and performed during follicular (FOL: days 2-7 or inactive pills) and luteal phases (LUT: day ~21 or 3rd week of active pills). Substrate oxidation was assessed via indirect calorimetry, blood lactate via finger stick, and recovery of skeletal muscle oxidative metabolism (mVO2) via continuous-wave near-infrared spectroscopy. HFF oxidized more fat (g·kg-1) during the full session (FOL: p = 0.050, LUT: p = 0.001), high intervals (FOL: p = 0.048, LUT: p = 0.001), low intervals (FOL: p = 0.032, LUT: p = 0.024), and LUT recovery (p = 0.033). Carbohydrate oxidation area under the curve was greater in HFF during FOL (FOL: p = 0.049, LUT: p = 0.124). Blood lactate was lower in LFF in FOL (p = 0.05) but not in LUT. Metabolic flexibility (delta fat oxidation g·kg-1·min-1) was greater in HFF than LFF during intervals 2-3 in FOL and 1-4 in LUT (p = 0.05). Fitness status more positively influences exercise metabolic flexibility during HIIE than cycle phase or OC use.